Removal of chromium from aqueous solution using apricot kernel/polyaniline /polyethylene glycol composite - Abdollah Sohrabi; Majid Riahi Samani; Davood Toghraie (Results in Engineering)
One of the main problems facing industrialized countries is the scarcity of water resources. Among the most significant inorganic pollutants found in industrial wastewater are heavy metals, whose concentrations often exceed permissible limits. It is essential to reduce the concentration of chromium (VI) in industrial wastewater to below these limits before discharging it into the environment.In this study, apricot kernels modified with polyaniline under various conditions were synthesized and utilized for the removal of Cr (VI). Additionally, the effects of various parameters, including adsorbent dosage, pH, contact time, and adsorption isotherms, were examined. The results indicated that the Cr removal performance of the apricot kernel/polyaniline composite synthesized in a water/ethanol solvent with 2 g/L of polyethylene glycol was favorable. This composite achieved its highest Cr removal percentage in the acidic range at pH=2; as pH increases, the Cr removal percentage decreases.The relationship between equilibration time and Cr (VI) removal percentage reveals that a contact duration of 30 min resulted in the highest Cr removal percentage. An increase in the adsorbent concentration from 2 g/L to 8 g/L led to a 95 % increase in the percentage of Cr (VI) removal. The results of the adsorption isotherm analysis indicate that the adsorption of Cr followed the Freundlich isotherm model.